Counter-Terrorism Laws and Human Rights in African Countries - John Mukum Mbaku (Washington University Global Studies Law Review, 2021)
The terrorist attacks on U.S. embassies in Dares Salaam (Tanzania) and Nairobi (Kenya) on August 7, 1998 made it clear to Africans that they were not immune from the rising tide of international terrorism. Eventually, many terrorist and extremist groups and organizations would emerge to become a major threat to peace and security in many parts of Africa. Today, organizations such as al-Qaeda in the Islamic Maghreb, Boko Haram/Islamic State in West Africa, and Al-Shabaab, continue to wreak havoc on African societies. In response to widespread terrorism and extremism, not just in Africa, but also around the world, the UN took action to establish legal mechanisms for the suppression and prevention of this international crime. In addition to establishing a committee dedicated to coordinating global efforts to confront terrorism, its perpetrators, and its supporters and financiers, the UN also adopted several conventions to fight this global crime, including the International Convention for the Suppression of the Financing of Terrorism, 1999. Taking a cue from the UN, the Organization of African Unity adopted the Convention on the Prevention and Combating of Terrorism on July 1, 1999 (Algiers Convention). As directed by the Algiers Convention, many African countries established criminal offenses for terrorist acts either by revising their national laws or enacting new statutes dedicated specifically to suppressing and preventing terrorism. It soon became evident, however, that each African country must balance its concern for peace and security with the need to protect the fundamental rights and freedoms of its citizens. International human rights scholars have argued that human rights principles and jurisprudence allow for sufficient flexibility to achieve a balance between security and human rights. Unfortunately, some African countries have been turning their anti-terrorism laws into tools for the violation of the fundamental rights and freedoms of their citizens. An examination of Maseko and Others v. the Prime Minister of Swaziland and Others, a case of the High Court of the Kingdom of Swaziland (Eswatini), reveals that through effective Bill ofRights litigation, national courts in the African countries can significantly improve the legal environment for fighting terrorism while, at the same time, minimizing the ability of national governments to use counter-terrorism laws as a tool of oppression.